NOXA upregulation by the prohibitin‐binding compound fluorizoline is transcriptionally regulated by integrated stress response‐induced ATF3 and ATF4. (26th July 2020) - Núñez‐Vázquez, Sonia; Sánchez‐Vera, Ismael; Saura‐Esteller, José; Cosialls, Ana M.; Noisier, Anaïs F.M.; Albericio, Fernando; Lavilla, Rodolfo; Pons, Gabriel; Iglesias‐Serret, Daniel; Gil, Joan
Abstract : Fluorizoline is a new synthetic molecule that induces p53‐independent apoptosis, in several tumor cell lines and in primary leukemia cells, by selectively targeting prohibitins (PHBs). In this study, we describe how fluorizoline induces BCL‐2 homology 3‐only protein NOXA, without modulating the protein levels of anti‐apoptotic B‐cell lymphoma‐2 (BCL‐2) family members prior to caspase activation, as well as how it synergizes with the BCL‐2 and BCL‐XL inhibitor ABT‐737 to induce apoptosis. Interestingly, fluorizolinetreatment triggers the activation of the integrated stress response (ISR) in HeLa and HAP1 cells, with increased eukaryotic translation initiation factor 2α phosphorylation, and induction of ATF3, ATF4, and CHOP. Moreover, PHB downregulation induces similar ISR activation and apoptosis as with fluorizoline treatment. In addition, we studied the essential role of the pro‐apoptotic protein NOXA in fluorizoline‐induced apoptosis and we describe its mechanism of induction in HeLa and HAP1 cells. Moreover, we identified ATF3 and ATF4 as the transcription factors that bind to NOXA promoter upon fluorizoline treatment. Furthermore, using ATF3 and ATF4 CRISPR HeLa and HAP1 cells, we confirmed that both factors mediate the induction of NOXA and apoptosis by fluorizoline. In conclusion, fluorizoline treatment triggers the activation of the ISR that results in the induction of ATF3 and ATF4, important regulators of NOXA transcription in fluorizoline‐induced apoptosis. Abstract : Fluorizoline is a new pro‐apoptotic agent that binds to prohibitins (PHB1 and PHB2) in the mitochondria and induces the integrated stress response (ISR). With phosphorylation of eukaryotic translation initiation factor 2α as the central event of this signaling pathway, fluorizoline induces ATF4 and ATF3. We demonstrated the key role of NOXA in fluorizoline‐induced apoptosis and identified ATF3 and ATF4 transcription factors as key mediators of NOXA upregulation and fluorizoline‐induced apoptosis.